A Erosão Praial na Costa Atlântica Uruguaia - PIVEL, MARÍA ALEJANDRA GÓMEZ; SPERANSKI, NIKOLAI; CALLIARI, LAURO JÚLIO (Pesquisas em Geociências, 2001)
The Uruguayan Atlantic coast is wave dominated. It appears as a sequence of beaches built between rocky headlands showing all ranges of morphodynamic behaviors from reflective to dissipative. Several beaches are undergoing erosion. All of them coincide with urbanized areas. In most cases the causes have not been established yet but there is no doubt that human activities have contributed to such problems. This fact raises the question about the nature of the erosion process. Does location of beaches under erosion on urbanized areas prove the man-induced origin of it? This paper discusses the possible factors involved on the beach erosion process. Sediment inputs to the beaches are limited. The inner shelf is likely to be the main source as it is covered with sandy sediments and shows a low gradient relief. The most significant continental source are the gullies although this remains a controversial issue as sediments eroded from them are usually finer than beach sediments. Anyway, as minor as it might be, this input contributes positively to the beach sediment budget. Sediment losses occur mainly by the inland migration of dunes and human activities. The latter includes the occupation of the backshore and frontal dunes, the building of seawalls, revetments and other hard structures to protect the houses, and the fixation of mobile dunes by planting. Pinus and Eucalyptus forests. Possible natural causes for beach erosion include storm surges and concentration of wave energy due to wave refraction. The latter hypothesis arouse in this research from wave refraction diagrams that showed a strong influence of the shelf relief on wave climate.